Extraction of Iron from the Rabbit Anterior Chamber with Reverse Iontophoresis - Shoubin Sun; Huijie Diao; Fali Zhao; Jianhai Bai; Yuan Zhou; Hao Cui; Liqiong Zhang (Journal of Ophthalmology)
Ocular siderosis is a common eye disease caused by retention of an iron-containing intraocular foreign body in the eye. Iron-containing intraocular foreign bodies may cause severe inflammatory reaction and affect visual function. Currently the optimal treatment method of ocular siderosis is a moot point. This study used the reverse iontophoresis technique to noninvasively extract iron from the rabbit anterior chamber. By slit lamp observation and histological examination, reverse iontophoresis treatment has a good effect on ocular siderosis. Reverse iontophoresis seems to be a noninvasive and promising approach to extract iron from the anterior chamber to treat ocular siderosis.